Resolvin D1 mitigates energy metabolism disorder after ischemia–reperfusion of the rat lung. Issue 1 (December 2016) - Zhao, Qifeng; Wu, Ji; Hua, Qingwang; Lin, Zhiyong; Ye, Leping; Zhang, Weixi; Wu, Guowei; Du, Jie; Xia, Jie; Chu, Maoping; Hu, Xingti
Abstract Background Energy metabolism disorder is a critical process in lung ischemia–reperfusion injury (LIRI). This study was aimed to determine the effects of resolvin D1 (RvD1) on the energy metabolism in LIRI. Methods Forty Sprague–Dawley rats were divided into the following groups: Sham group; untreated ischemia–reperfusion (IR) control; IR treated with normal saline (IR-NS); and IR treated with RvD1 (IR-RV) (100 μg/kg, iv). LIRI and energy metabolism disorder were determined in these rats. Results The results revealed that the levels of interleukin (IL)-1β, tumor necrosis factor-α, IL-10, monocyte chemoattractant protein-1, macrophage inflammatory protein-2, cytokine-induced neutrophil chemoattractant-1, injured alveoli rate, apoptosis index, pulmonary permeability index, malondialdehyde, ADP, and lactic acid were increased, whereas the levels of ATP, ATP/ADP, glycogen, Na+ –K+ -ATPase, superoxide dismutase, glutathione peroxidase activity, pulmonary surfactant associated protein-A, and oxygenation index were decreased in rats with LIRI. Except for IL-10, all these biomarkers of LIRI and its related energy metabolism disorder were significantly inhibited by RvD1 treatment. In addition, histological analysis via hematoxylin–eosin staining, and transmission electron microscopy confirmed that IR-induced structure damages of lung tissues were reduced by RvD1. Conclusion RvD1 improves the energy metabolism of LIRI disturbance, protects the mitochondrial structure and function, increases the ATP, glycogen content and Na+ –K+ -ATPase activity of lung tissue, balances the ratio of ATP/ADP and finally decreases the rate of apoptosis, resulting in the protection of IR-induced lung injury. The improved energy metabolism after LIRI may be related to the reduced inflammatory response, the balance of the oxidative/antioxidant and the pro-inflammatory/anti-inflammatory systems in rats.